The conformity of Maturidiyah Theology to Sunni Islam with the Shafi'i school of thought - Mustafa Kamil Thahir (Journal of Social Research, 2025)
This paper explores the theological framework of Maturidiyah and its compatibility with the Shafi’i school of thought, focusing on ways to bridge the understanding and acceptance of Maturidiyah principles among Shafi’i adherents. Both theological traditions share a Sunni foundation, yet they differ on key issues such as the role of reason in faith, the concept of divine attributes, and the interplay between predestination (qadar) and free will. The study emphasizes the importance of highlighting shared values, such as the commitment to Ahl al-Sunnah wa al-Jama’ah and the balance between textual evidence (naql) and rational inquiry (aql). It argues that Maturidiyah theology’s rational approach to faith and its nuanced view of divine justice and human agency can enrich the spiritual and intellectual framework of Shafi’i believers without undermining their core principles. Through historical analysis and comparative theology, the paper provides strategies for presenting Maturidiyah as a complementary perspective rather than a conflicting one. Practical recommendations include inter-school dialogues, educational programs, and mentorship initiatives led by scholars grounded in both traditions. Ultimately, the paper underscores the significance of fostering unity and mutual understanding in addressing contemporary challenges faced by the Muslim community.